Kierkegaard's Romantic Legacy Two Theories of the Self - Gupta, Anoop (Philosophica, 2005)
In Kierkegaard's Romantic Legacy, Anoop Gupta develops an original theory of the self based on Kierkegaard's writings. Gupta proceeds by historical exegesis and considers several important ways of thinking about self outside of the natural sciences. His study moves theories of the self from theology toward sociology, from a God-relationship to a social one, and illustrates how a loss in theological underpinnings partly contributes to the rise in the popularity of cultural relativism. By drawing on Kierkegaard's writings, Gupta develops a metaphysical account of the self that provides an alternative to the idea that there is no such thing as human nature.